La zona republicana se parte en dos : (Abril 1938) / [redacción Javier Redondo... (et al.)] - Redondo Rodelas, Javier (La guerra civil Española mes a mes ; 24)
Contiene "Semblanzas" de : Indalecio Prieto, Wilhelm Canaris, Manuel Machado, Carrasco i Formiguera, Miguel Hernández, Sagardía Ramos, Kati Horna, Julián Zugazagoitia, El Conde Ziano